E-AVIATION LAW MODUL FOR AVIATION VOCATION SCHOOL - Sekar Gading, Nilam; Fatmawati, Fatmawati (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Aviation Law is one of the courses in the Aeronautical Communication Diploma 3 Study Program that studies national and international aviation regulations, which aims to enable cadets to explain the regulations that apply nationally and internationally in the work area to guide aviation communication in all classifications of airspace in aviation. In the development of information and communication technology in Indonesia, educational learning media through applications or websites that make learning activities more interesting, effective and efficient. At this time, learning Aviation Law Subjects still uses modules that are less interactive referenced documents so that cadets quickly feel bored and less interested in carrying out learning. So in this industrial revolution 4.0 to realize effective and enjoyable learning, the author suggests making e-modules. In this study using the type of research and with the Waterfall method. The results of this research are E-modules of Aviation Law in the form of flipbooks and mastery tests contained in each topic of discussion which are equipped with images, video, and sound that have been adjusted to the academic syllabus and implemented on the Learning Management System (LMS) in Aviation Polytechnic of Surabaya. The author's goal in this final project is to design and create e-aviation law modules as new interesting and innovative learning media that can help in aviation law learning